MicroRNA-23a/24-2/27a as a potential diagnostic biomarker for cancer: A systematic review and meta-analysis - Quan, Jing (Mol Clin Oncol, 2018)
An increasing number of studies have proven that microRNAs play an important role in the occurrence, development and prognosis of various types of cancer. As a vital gene cluster, the microRNA (miR)-23a/24-2/27a cluster may be an important marker for predicting cancer prognosis and tumor progression. A search was conducted through PubMed, Medline and the Cochrane Library to identify studies investigating the association between the miR-23a/24-2/27a cluster and cancer, and the identified related studies were included in the present meta-analysis. The strength of the association was assessed by hazard ratio (HR) and its 95% confidence interval (95% CI). A total of 21 studies were included in this meta-analysis. The results indicated that a high level of miR-23a exerted a significant effect on overall survival (OS) (HR=2.33, 95% CI: 1.18–4.58; P=0.014), but not on disease-free survival (DFS)/recurrence-free survival (RFS) (HR=1.13, 95% CI: 0.37–3.44; P=0.836). There was an obvious statistically significant association between OS and the expression of miR-24 (HR=2.49, 95% CI: 1.84–3.37; P=0.000), particularly in the digestive system (pooled HR=2.99, 95% CI: 2.17–4.13, P=0.000). In addition, the result suggested a statistically significant association between the expression of miR-27a and OS (pooled HR=1.89, 95% CI: 1.32–2.69; P=0.001), as well as DFS/RFS/progression-free survival (HR=2.19, 95% CI: 1.29–3.70; P=0.003), particularly in renal cell carcinoma (HR=2.30, 95% CI: 1.16–4.67; P=0.017). A subgroup analysis by ethnicity, cancer type and statistical methodology was performed. There was no obvious publication bias. In conclusion, the present study demonstrated that the miR-23a/24-2/27a cluster may be a useful marker for predicting cancer prognosis and tumor progression.